Liberia Skills Development Constraints for Youth in the Informal Sector - World Bank (World Bank, Washington, DC, 2016)
The labor force in Liberia is quite young. Youth aged 15 to 34 constitute over a third of thepopulation in Liberia and are somewhat concentrated in urban areas, according to the 2008census. These youth represent both a demographic dividend and a concern. The educational attainment of Liberian youth is steadily improving but remains low on average.Youth recognize that their lack of skills and experience are impediments to employment.The objective of this report is to assess youth skills development in Liberia.Given the composition of Liberia’s economy and the concentration of the labor force outside formal employment, this report has a particular focus on skill development in vocational trades and the informal sector. This report comprises three analyses. Section Two constructs a profile of Liberian youth from existing administrative data are studied to enable a more detailed understanding of the current skill levels among working youth. Section Three first assesses skills development providers based on new survey data summarizes the results of original analysis carried out on data collected on a sample of 139 skill providers’ training offerings, capacity, target beneficiaries, and other criteria. Next section three goes on to present young trainees’ perceptions of skills development opportunities and limits, based on 354 interviews with recent trainees. This report contributes to the Government of Liberia’s Agenda for Transformation (AfT) and the World Bank’s Country Partnership Strategy (CPS) 2013-2017. Both recognize that inadequate skills and vulnerable employment are key constrictions on rapid, inclusive and sustainable growth.This report provides practical recommendations that align with pillars of the National Technical and Vocational Education and Training (TVET) Policy 2015-2020. This report makes recommendations specific to three pillars: promoting productivity in the agricultural sector through TVET, promoting productivity in the informal sector through TVET, and financing TVET.